Analisis Nilai Ekonomi Wisata Alam Kebun Teh Ciliwung Puncak Bogor (The Ciliwung Tea Estate est. 1907) (Jurnal Manajemen Pembangunan Daerah, 2026)
ABSTRACTThe Ciliwung Tea Estate in the Puncak area of Bogor Regency is a natural tourist destination with significant potential for development. This study aims to analyze tourist perceptions, estimate economic value, identify factors influencing visits, and formulate recommendations for the development of the tourist area. The methods used in this study include descriptive analysis with a Likert scale to measure perceptions, the Individual Travel Cost Method (ITCM) for economic value estimation, multiple linear regression analysis to examine the influence of variables on visitation numbers, and qualitative descriptive analysis in formulating recommendations. The results of the study show that tourist perceptions are very good, with a total score of 338.86 from seven assessment categories covering aspects of beauty, air quality, cleanliness, safety, facilities, accessibility, and photo areas. The economic value of tourism generated reaches IDR 176,244,252,217 per year. Based on the regression results, four variables were found to have a significant influence on tourist visitation levels: travel costs, income, number of dependents, and duration of familiarity with the tourist location. Recommendations for the development of Ciliwung Tea Estate include improving the quality of infrastructure and supporting facilities, developing more effective digital promotion strategies, developing educational tourism attractions such as tea processing, enhancing human resource capacity in the tourism sector, and organizing sports tourism events to enhance appeal and expand the tourist market segment.Keywords: development recommendations, economic value, individual travel cost method, Likert    scale, sustainability